KAJIAN PUSTAKA : FAKTOR TERJADINYA HAND ARM VIBRATION SYNDROME PADA PEKERJA - Taufik Dwinaffebri; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2021)
Workers who;useuhand-held vibratory devices have the potential to experience occupational diseases, especially Hand Arm Vibration Syndrome (HAVS). Thisistudy wasaaimed to analyzejthe relationshipnbetween theafactors;of age, length of service, length and exposure to arm vibration and complaints of;Hand;Arm;Vibration Syndrome in;workers.uThe method used in this research was a literature review study. The literature were conducted online through several website or internet sites such asResearchgate, ScienceDirect, and Google Scholar. This research was conducted on 11 articles consisting of 5 national and 6 international articles. The resultuofvthis studyuindicate thatuthe factor of age, length of service, length and  exposure to arm vibration have a significant relationship with complain of hand arm vibration syndrome in workers. From all research, article obtained related to factor of age, length of service, length and  exposure to arm vibration have a significant relationship with complain of HAVS.